2016
DOI: 10.21037/sci.2016.08.07
|View full text |Cite
|
Sign up to set email alerts
|

The DARC-CD82 axis discloses bone marrow macrophages as guardians of long-term hematopoietic stem cells quiescence

Abstract: Hernández Á. The DARC-CD82 axis discloses bone marrow macrophages as guardians of long-term hematopoietic stem cells quiescence. Stem Cell Investig 2016;3:44.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…CD82 also upregulates the expression level and the formation of integrin α4β1 cluster causing increased adhesion to BM microenvironment (6). Based on these studies, as Pérez-Fernández et al suggested (2), it is conceivable that CD82 may put HSCs to sleep not only by TGFβ-SMAD3 pathway Correspondence Shedding light on the DARC knight as a guardian of hematopoietic stem cell quiescence but also by promoting spatial rearrangement of adhesion molecules which favors HSC-to-niche interaction and concomitant cell cycle exit.…”
Section: Cd82: Functional Marker For Adult Stemprogenitor Cells?mentioning
confidence: 90%
See 1 more Smart Citation
“…CD82 also upregulates the expression level and the formation of integrin α4β1 cluster causing increased adhesion to BM microenvironment (6). Based on these studies, as Pérez-Fernández et al suggested (2), it is conceivable that CD82 may put HSCs to sleep not only by TGFβ-SMAD3 pathway Correspondence Shedding light on the DARC knight as a guardian of hematopoietic stem cell quiescence but also by promoting spatial rearrangement of adhesion molecules which favors HSC-to-niche interaction and concomitant cell cycle exit.…”
Section: Cd82: Functional Marker For Adult Stemprogenitor Cells?mentioning
confidence: 90%
“…In-depth understanding of the crosstalk between hematopoietic stem cells (HSCs) and their niche, and identification of 'functional' surface markers of HSCs are vital in the advancement of therapies for hematological disorders (e.g., ex vivo expansion or transplantation of HSCs). MacNamara (1) and Pérez-Fernández et al (2) respectively provided constructive comments on our results and made very interesting suggestions regarding clinical application of the CD82/DARC axis. In this Correspondence, we aim to add to the discussion (1,2) on our recent article (3).…”
mentioning
confidence: 85%